2016
DOI: 10.1016/j.biombioe.2016.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable use of eucalypt biomass grown on short rotation coppice for bioenergy

Abstract: Bioenergy is one of the alternatives to reduce the dependence of global energy on fossil fuels. The short rotation coppice (SRC) of eucalypt species appears as an interesting option for forest biomass production in a short time. However, the harvesting of whole trees (included the crown) in SRC systems has implications on sustainable land use. More information is required on the increase of biomass as renewable energy resource to achieve the sustainability of these crops. The main objective of this research wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 31 publications
3
28
0
2
Order By: Relevance
“…Some plants have shown potential to be used as sources of bioenergy, namely: elephant grass (Daher et al, 2014;Rocha et al, 2015;Salazar-Zeledón et al, 2015;Ghosh, 2016;Menezes et al, 2016), sugarcane (Szczerbowski et al, 2014;Bordonal et al, 2015), sorghum (Silva et al, 2016), and eucalyptus (Eufrade Junior et al, 2016). However, in contrast to elephant grass, which shows high photosynthetic efficiency with high biomass productivity potential, some of these cultures show low dry biomass production.…”
Section: Introductionmentioning
confidence: 95%
“…Some plants have shown potential to be used as sources of bioenergy, namely: elephant grass (Daher et al, 2014;Rocha et al, 2015;Salazar-Zeledón et al, 2015;Ghosh, 2016;Menezes et al, 2016), sugarcane (Szczerbowski et al, 2014;Bordonal et al, 2015), sorghum (Silva et al, 2016), and eucalyptus (Eufrade Junior et al, 2016). However, in contrast to elephant grass, which shows high photosynthetic efficiency with high biomass productivity potential, some of these cultures show low dry biomass production.…”
Section: Introductionmentioning
confidence: 95%
“…For example, in tropical and sub-tropical climates, elephant or Napier grass (Pennisetum purpureum) produces more biomass per hectare annually than any other vegetation. Grasses like Miscanthus × giganteus, sorghum, and switchgrass (Panicum virgatum), and tree species like poplar, aspen, and willow are capable of producing large amounts of biomass in temperate regions like Europe and the United States (Heaton et al, 2008;Guidi et al, 2013;Junior et al, 2016). While the massive bioethanol productivity of Brazil comes from sugarcane sucrose, the lignocellulosic biomass left over could additionally be engineered for better bioenergy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Other environmental impacts are reported, varying mostly due to technical aspects of the chosen bioenergy system (e.g., biomass production system, transportation, plant efficiency and technology), modelling assumptions, and methodological issues (e.g., methods to deal with the coproducts) [17][18][19]28].High-density energy wood plantations managed on short-rotation coppice (SRC) are seen as a promising source of biomass for different final uses, since they could help to mitigate some of the environmental issues arising from using forest wood resources for bioenergy [17,18,39,40]. It is mostly because SRC production systems present relatively higher yields than conventional forestry systems [39], and the possibility to be gown on marginal land to reverse grassland degradation, thereby being beneficial under both a climate change mitigation and land restoration perspective [16,41].To the best of our knowledge, no previous studies examined the environmental implications of alternative energy and transportation services in Europe form novel technologies and pioneering eucalyptus short-rotation coppice (SRC) systems in Brazil. This research gap is particularly important because many global temperature stabilization scenarios aligning with a 2 or 1.5 • C target predict a large increase in the biomass supply to the international markets, especially from land-rich regions, such as Latin America and Africa, to high energy-demanding regions, such as Europe and East Asia [2,3,42,43].…”
mentioning
confidence: 99%
“…The environmental conditions and locations in which biomass resources grow considerably affect yields, management systems, and the product characteristics [40]. Wood pellets from eucalyptus SRC produced in Brazil are a promising option because eucalyptus is the most important forest species for wood supply in the country [39], and plantation trials have demonstrated that it is possible to double productivity when eucalyptus is grown under SRC management [45].In this study, we apply the life cycle assessment (LCA) methodology to quantify relevant environmental impacts of different bioenergy systems delivering energy and transportation services in Europe from imported wood pellets from pioneering eucalyptus SRC systems produced in Brazil, including production of heat, electricity, advanced liquid biofuels, and BECCS. Using this approach, we aim to determine the best bioenergy systems to convert biomass resources in energy and transportation services in Europe, identify the supply chain stages with higher environmental impacts, and compare the environmental benefits and adverse side effects of bioenergy displacing fossil fuel products.…”
mentioning
confidence: 99%
See 1 more Smart Citation